INVESTIGATING PROBLEMS FACED BY STUDENTS IN SPEAKING ENGLISH LANGUAGE - Sampurno, Cahyo Budi; Rafiqa, Syarifa; Silaban, Ramot (Universitas Borneo Tarakan, 2024)
This study investigates the problems faced by students in speaking English, focusing on linguistic, psychological, and motivational challenges. Speaking is a crucial skill in English language learning, yet many students struggle due to limited vocabulary, difficulties in constructing sentences, and pronunciation issues. Psychological barriers such as lack of confidence, fear of making mistakes, and low motivation further hinder their speaking abilities. Using a descriptive qualitative design, data were collected through questionnaires distributed to 37 Grade 11 students and interviews with 5 selected participants from SMAN 1 Tarakan. The findings reveal that students’ difficulties are multifaceted, encompassing linguistic issues and deeper psychological concerns, compounded by a lack of early exposure to English and disinterest in the subject. Addressing these challenges requires a holistic approach involving targeted practice, a supportive learning environment, bridging programs, and engaging teaching strategies to enhance students’ speaking skills and motivation in learning English.